Battery cells, battery cell preparation methods and electrical devices

CN122992007APending Publication Date: 2026-10-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510529338.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]采用水系正极浆料制备二次电池具有降低成本、减少环境污染、降低溶剂对电化学性能的负面影响的优点,然而,制备的二次电池存在正极活性材料初始充放电克容量低的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992007A_ABST
    Figure CN122992007A_ABST
Patent Text Reader

Abstract

This application provides a battery cell, a method for preparing the battery cell, and an electrical device. The positive electrode of the battery cell is an aqueous electrode, and the positive electrode active material includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof. The positive electrode of this battery cell is prepared using an aqueous positive electrode slurry, which helps to reduce costs, reduce environmental pollution, and reduce the negative impact of solvents on electrochemical performance. Furthermore, the positive electrode active material has excellent initial charge-discharge specific capacity, and the battery cell has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary battery technology, and in particular to a battery cell, a method for preparing the battery cell, and an electrical device thereof. Background Technology

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.

[0003] Using aqueous cathode slurry to prepare secondary batteries has the advantages of reducing costs, reducing environmental pollution, and reducing the negative impact of solvents on electrochemical performance. However, the prepared secondary batteries have the problem of low initial charge-discharge specific capacity of the cathode active material. Summary of the Invention

[0004] This application was made in view of the aforementioned issues and aims to at least solve one of the technical problems existing in the prior art. Therefore, this application provides a battery cell, a method for manufacturing the battery cell, and an electrical device.

[0005] The first aspect of this application provides a battery cell, the battery cell including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer including a positive electrode active material, wherein the positive electrode sheet is an aqueous electrode sheet;

[0006] The positive electrode active material includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

[0007] Compared to oil-based cathode slurries, using aqueous cathode slurries to prepare battery cells is advantageous in reducing costs and environmental pollution. It also avoids the impact of residual oily solvents (e.g., N-methylpyrrolidone) in the film layer on electrochemical performance, which is a consequence of using oil-based cathode slurries. However, battery cells prepared using aqueous cathode slurries face the challenge of low initial charge-discharge specific capacity of the cathode active material. Analysis suggests this may be because during the preparation of aqueous cathode slurries, active ions (e.g., lithium ions) in the cathode active material matrix (e.g., lithium transition metal phosphates) undergo a displacement reaction with hydrogen ions, leading to their dissolution and irreversible loss, thus causing a deterioration in the initial charge-discharge specific capacity. Therefore, the positive electrode active material of the battery cell in this application includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. This coating layer helps to reduce the contact between the positive electrode active material matrix and water during the preparation of the aqueous positive electrode slurry, thereby reducing the displacement reaction between active ions and hydrogen ions in the matrix, reducing the dissolution of active ions, and thus improving the initial charge-discharge specific capacity of the positive electrode active material. Furthermore, compared to the method of adding a lithium replenishing agent to the positive electrode sheet to compensate for the loss of active ions (e.g., lithium ions) and thus improve the initial charge-discharge specific capacity, the positive electrode active material of this application reduces the dissolution of active ions, thereby reducing the damage to the matrix structure and helping to improve the structural stability of the matrix, thus also improving the cycle stability of the battery cell. Moreover, the phthalocyanine complex is stable, non-toxic, and inexpensive, and can promote charge transfer, making the coating layer help to increase the active ion transport channels, increase the active ion diffusion rate, and thus improve the electrochemical stability of the positive electrode active material, which is beneficial to further improving the cycle stability of the battery cell.

[0008] In any embodiment, the matrix is ​​selected from lithium-containing transition metal phosphates.

[0009] Lithium-containing transition metal phosphates are suitable for the preparation of aqueous cathode slurries, which is beneficial for further improving the cycle stability of battery cells prepared from aqueous cathode slurries.

[0010] In any embodiment, the I of the positive electrode film D / I G It is 0.5-1.55, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

[0011] I of the positive electrode film D / I GWithin the aforementioned range, it is evident that the outer side of the core of the positive electrode active material is successfully coated with a coating layer including phthalocyanine complexes, which helps to improve the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0012] In any implementation, the kernel's I D / I G It ranges from 0.7 to 1.3.

[0013] In any embodiment, the phthalocyanine complex accounts for 0.1%-2% of the total mass of the positive electrode active material.

[0014] Based on the total mass of the positive electrode active material, when the mass ratio of the phthalocyanine complex is within the above range, it helps to improve the cycle stability of the battery cell while the positive electrode active material also has a better initial charge-discharge capacity.

[0015] In any implementation, the kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, which is 0.7-1.0.

[0016] And / or,

[0017] The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, which is 1.0-1.3.

[0018] When the I of the core of the positive electrode active material D / I G When the value is 0.7-1.0, it indicates that the graphitization degree of the core surface is relatively high, the coating integrity of the carbon coating layer is good, and the contact area between the core and the aqueous solvent is small. This reduces the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions. Therefore, when the mass ratio of phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, the cycle stability of the battery cell can be improved, and the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0019] When the kernel's I D / I GWhen the value is 1.0-1.3, it indicates that the graphitization degree of the core surface is low, the integrity of the carbon coating layer is poor, and the contact area between the core and the aqueous solvent is large. As a result, the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions is high. Therefore, when the mass ratio of phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, it helps to improve the cycle stability of the battery cell. At the same time, the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0020] In any embodiment, the phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, or manganese phthalocyanine.

[0021] In any embodiment, the thickness of the coating layer is 150nm-500nm, and can be selected as 200nm-400nm.

[0022] When the thickness of the coating layer is within the above range, it helps to improve the cycle stability of the battery cell, while the positive electrode active material also has better initial charge and discharge specific capacity and kinetic performance, which helps to alleviate polarization and comprehensively improves the electrochemical performance of the battery.

[0023] In any embodiment, the volume distribution particle size Dv50 of the positive electrode active material is 0.5 μm-5 μm; and / or

[0024] The volume distribution particle size Dv99 of the positive electrode active material is 10μm-15μm.

[0025] In any embodiment, the positive electrode film layer further includes a binder, the binder comprising one or more of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

[0026] The aforementioned binder helps to enhance the adhesion between the positive electrode film layer formed by the aqueous positive electrode slurry and the current collector, thereby helping to further improve the cycle stability of the battery cell.

[0027] In any embodiment, the lithium transition metal phosphate comprises a component having the following general formula:

[0028] Li m A a Fe x D d P y E e O z G g ,

[0029] The A element comprises at least one element selected from Al, Na, K, or Mg; the D element comprises at least one element selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti, or V; the E element comprises at least one element selected from B, S, Si, or N; the G element comprises at least one element selected from S, F, Cl, or Br; the m element is selected from the range of 0.5 to 1.15; the a element is selected from the range of 0 to 0.1; the x element is selected from the range of 0.5 to 1; the d element is selected from the range of 0 to 0.5; the y element is selected from the range of 0.5 to 1; the e element is selected from the range of 0 to 0.5; the z element is selected from the range of 3.5 to 4; and the g element is selected from the range of 0 to 0.5.

[0030] A second aspect of this application provides a method for preparing a battery cell, the method comprising at least the following steps:

[0031] A positive electrode active material is obtained, the positive electrode active material comprising a core and a coating layer covering at least a portion of the surface of the core, the coating layer comprising a phthalocyanine complex;

[0032] A mixture comprising the positive electrode active material and water is obtained to obtain an aqueous positive electrode slurry;

[0033] Battery cells were prepared using the aforementioned aqueous cathode slurry;

[0034] The core comprises a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

[0035] Compared to oil-based cathode slurries, using aqueous cathode slurries to prepare battery cells is advantageous in reducing costs and environmental pollution. It also avoids the impact of residual oily solvents (e.g., N-methylpyrrolidone) in the film layer on electrochemical performance, which is a consequence of using oil-based cathode slurries. However, battery cells prepared using aqueous cathode slurries face the challenge of low initial charge-discharge specific capacity of the cathode active material. Analysis suggests this may be because during the preparation of aqueous cathode slurries, active ions (e.g., lithium ions) in the cathode active material matrix (e.g., lithium transition metal phosphates) undergo a displacement reaction with hydrogen ions, leading to their dissolution and irreversible loss, thus causing a deterioration in the initial charge-discharge specific capacity.

[0036] Phthalocyanine complexes possess an 18π-electron conjugated structure, exhibiting strong coordination ability and redox properties. This allows the six-membered rings of the phthalocyanine complex to undergo π-π stacking within themselves. Furthermore, the phthalocyanine complex itself contains multiple six-membered rings, which can continue to stack π-π with the six-membered rings of the carbon coating layer on the substrate surface, thereby achieving stable coating of the core of the positive electrode active material. The method for preparing the battery cell in this application utilizes the aforementioned positive electrode active material, which helps to reduce the contact between the positive electrode active material substrate and water during the preparation of aqueous positive electrode slurry, thereby reducing the displacement reaction between active ions and hydrogen ions in the substrate, reducing the dissolution of active ions, and improving the initial charge-discharge specific capacity of the positive electrode active material. Compared to the method of adding lithium replenishing agents to the positive electrode sheet to compensate for the loss of active ions (e.g., lithium ions) and thus improve the initial charge-discharge specific capacity, the positive electrode active material of this application reduces the dissolution of active ions, thereby reducing the damage to the substrate structure and helping to improve the structural stability of the substrate, thus also improving the cycle stability of the battery cell. Furthermore, phthalocyanine complexes are stable, non-toxic, and inexpensive, and can promote charge transfer. This allows the coating layer containing phthalocyanine complexes to increase the active ion transport channels and improve the active ion diffusion rate, thereby enhancing the electrochemical stability of the positive electrode active material and further improving the cycle stability of the battery cell.

[0037] In any embodiment, the matrix is ​​selected from lithium-containing transition metal phosphates.

[0038] Lithium-containing transition metal phosphates are suitable for the preparation of aqueous cathode slurries, which is beneficial for further improving the cycle stability of battery cells prepared from aqueous cathode slurries.

[0039] In any embodiment, obtaining the positive electrode active material includes:

[0040] The positive electrode active material is obtained by treating the core and the phthalocyanine complex using one or more of the following processes: dry mixing, ultrasonic processing, magnetron sputtering, dot coating, and dip coating.

[0041] All of the above processes can achieve stable coating of the core by phthalocyanine complexes, thereby reducing the irreversible loss of active ions and the damage to the matrix structure during the preparation of aqueous cathode slurry, and thus improving the initial charge-discharge specific capacity of the cathode active material and the cycle stability of the battery.

[0042] In any embodiment, the preparation method includes at least the following steps:

[0043] The core and the phthalocyanine complex are dry-mixed to obtain the positive electrode active material;

[0044] A mixture comprising the positive electrode active material and water is obtained to obtain the aqueous positive electrode slurry.

[0045] Using a dry mixing process helps to further improve the coating stability of phthalocyanine complexes on the core. The dry mixing process can also reduce damage to the matrix structure, control the coating amount of phthalocyanine complexes to a moderate level, and thus further improve the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery. Furthermore, the dry mixing process is suitable for industrial applications.

[0046] In any implementation, the kernel's I D / I G It is 0.7-1.3, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

[0047] In any embodiment, the phthalocyanine complex accounts for 0.1%-2% of the total mass of the positive electrode active material.

[0048] Based on the total mass of the positive electrode active material, when the mass ratio of the phthalocyanine complex is within the above range, it helps to improve the cycle stability of the battery cell while the positive electrode active material also has a better initial charge-discharge capacity.

[0049] In any implementation, the kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, which is 0.7-1.0.

[0050] And / or,

[0051] The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, which is 1.0-1.3.

[0052] When the I of the core of the positive electrode active material D / I GWhen the value is 0.7-1.0, it indicates that the graphitization degree of the core surface is relatively high, the coating integrity of the carbon coating layer is good, and the contact area between the core and the aqueous solvent is small. This reduces the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions. Therefore, when the mass ratio of phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, the cycle stability of the battery cell can be improved, and the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0053] When the kernel's I D / I G When the value is 1.0-1.3, it indicates that the graphitization degree of the core surface is low, the integrity of the carbon coating layer is poor, and the contact area between the core and the aqueous solvent is large. As a result, the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions is high. Therefore, when the mass ratio of phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, it helps to improve the cycle stability of the battery cell. At the same time, the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0054] In any embodiment, the phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, and manganese phthalocyanine.

[0055] In any embodiment, the preparation method includes at least the following steps:

[0056] The core and phthalocyanine complex are dry-mixed to obtain the positive electrode active material;

[0057] A mixture comprising the positive electrode active material, water, and binder is obtained to obtain the aqueous positive electrode slurry.

[0058] Dry mixing the core and phthalocyanine complex, followed by mixing with water and binder, helps to further reduce the displacement reaction between active ions and hydrogen ions in the positive electrode active material matrix, further reducing the dissolution of active ions and damage to the matrix structure, thereby further improving the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0059] In any embodiment, the binder comprises one or more of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

[0060] The aforementioned binder helps to enhance the adhesion between the positive electrode film layer formed by the aqueous positive electrode slurry and the current collector, thereby helping to further improve the cycle stability of the battery cell.

[0061] In any embodiment, the mixture further includes one or more of a conductive agent and a dispersant.

[0062] In any embodiment, the preparation method includes at least the following steps:

[0063] The core and the phthalocyanine complex are first dry-mixed to obtain the positive electrode active material;

[0064] The positive electrode active material and the conductive agent are subjected to a second dry mixing to obtain a first mixture;

[0065] The first mixture, the dispersant, and water are first mixed to obtain a second mixture;

[0066] The second mixture and the binder are mixed a second time to obtain the mixture, thus obtaining the aqueous positive electrode slurry.

[0067] The above preparation process helps to improve the coating stability of the core by the phthalocyanine complex, uniformly mix the positive electrode active material, conductive agent, dispersant and binder, thereby realizing the role of conductive agent, dispersant and binder, and further improving the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0068] In any embodiment, the rotational speed of the first dry mixer is 300 r / min-1500 r / min, optionally 500 r / min-800 r / min; and / or,

[0069] The second dry mixing speed is 300 r / min-1500 r / min, optionally 500 r / min-800 r / min; and / or,

[0070] The rotational speed of the first mixing is 200 r / min-1800 r / min, optionally 800 r / min-1200 r / min; and / or,

[0071] The rotational speed of the second mixing is 200 r / min-1800 r / min, and can be selected as 800 r / min-1200 r / min.

[0072] The aforementioned rotational speed helps to balance the coating stability of the phthalocyanine complex on the core and the structural integrity of the core, uniformly mix the positive electrode active material, conductive agent, dispersant and binder, thereby realizing the functions of the conductive agent, dispersant and binder, and further improving the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0073] In any embodiment, the solid content of the aqueous positive electrode slurry is 50%-70%; and / or,

[0074] The viscosity of the aqueous cathode slurry is 3000 mPa·s-9000 mPa·s.

[0075] When the solid content of the aqueous cathode slurry is within the above range, the aqueous cathode slurry has excellent stability and dispersibility, the slurry is not prone to sedimentation, and it has excellent coating performance, which is conducive to the spreading of the slurry.

[0076] When the viscosity of the aqueous cathode slurry is within the above range, the aqueous cathode slurry has excellent stability and dispersibility, excellent coating performance, suitable drying time after coating, and uniform electrode stress, making it less prone to cracking.

[0077] A third aspect of this application provides an electrical device comprising a battery cell according to the first aspect of this application or a battery cell prepared according to the preparation method of the second aspect of this application. Attached Figure Description

[0078] Figure 1 The images shown are transmission electron microscope (TEM) images (left) and elemental mapping spectra (right) of the positive electrode active material prepared in Example 1 of this application.

[0079] Figure 2 This is a transmission electron microscope image of the positive electrode active material prepared in Example 1 of this application;

[0080] Figure 3 This is a schematic diagram of a battery cell according to one embodiment of this application;

[0081] Figure 4 yes Figure 3 An exploded view of a battery cell according to one embodiment of this application is shown.

[0082] Figure 5 This is a schematic diagram of a battery module according to one embodiment of this application;

[0083] Figure 6 This is a schematic diagram of a battery pack according to one embodiment of this application;

[0084] Figure 7 yes Figure 6 An exploded view of a battery pack according to one embodiment of this application is shown;

[0085] Figure 8 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.

[0086] Explanation of reference numerals in the attached figures:

[0087] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation

[0088] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the battery cell, the method for preparing the battery cell, and the electrical device thereof. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0089] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0090] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0091] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0092] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0093] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0094] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0095] Compared to traditional oil-based cathode slurries, aqueous cathode slurries can reduce the use of oily solvents such as N-methyl-2-pyrrolidone (NMP) and fluorinated oily binders, thereby reducing slurry costs, environmental pollution, and the negative impact of solvents on electrochemical performance. However, battery cells prepared with aqueous cathode slurries suffer from low initial charge-discharge specific capacity of the cathode active material.

[0096] [Battery cell]

[0097] Based on this, this application provides a battery cell, the battery cell including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer including a positive electrode active material, wherein the positive electrode sheet is an aqueous electrode sheet;

[0098] The positive electrode active material includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

[0099] In this paper, the term "phthalocyanine complex" refers to a complex formed by the coordination of phthalocyanine with an element. Phthalocyanine is a molecular structure consisting of four pyrrole nuclei forming a porphyrin ring, exhibiting a stable conjugated system. The phthalocyanine ring contains a cavity, and the two hydrogen atoms within this central cavity can be replaced by more than 70 elements to form phthalocyanine complexes. These elements include almost all metallic elements and some non-metallic elements.

[0100] In this article, the term "aqueous electrode" refers to a battery electrode prepared in an aqueous solvent system.

[0101] In this paper, the coating layer of the positive electrode active material can be measured using methods and equipment known in the art. As an example, the positive electrode sheet of the battery in its initial state or after cycling is disassembled, the positive electrode film layer of the positive electrode sheet is peeled off, and the positive electrode film layer is thoroughly washed with acetone to remove binders and dispersants, etc., in the positive electrode film layer. After filtration and drying, the positive electrode active material powder is obtained. The coating layer on the surface of lithium iron phosphate can be observed by ion polishing cross-sectional morphology analysis (CP), combined with scanning electron microscopy (SEM) and transmission electron microscopy (TEM). X-ray energy dispersive spectroscopy (EDS) is used for surface scanning (the surface scanning elements are selected according to the elements to be measured) to obtain the corresponding mapping spectrum, which can test the coordination elements on the surface of the positive electrode active material, including phthalocyanine complexes.

[0102] In this paper, the positive electrode is an aqueous electrode, which can be measured using methods and equipment known in the art. As an example, the battery cell is disassembled, the positive electrode is separated, and cut into 5cm*5cm electrodes. The electrodes are then placed separately in NMP. After 1 hour, the film area of ​​the oil-based electrode completely falls off, leaving only the current collector foil, while the film area of ​​the aqueous electrode does not fall off.

[0103] In some embodiments, the battery cell includes a lithium-ion battery, and the substrate includes a lithium-containing transition metal phosphate.

[0104] In some embodiments, the battery cell includes a sodium-ion battery, and the matrix includes a sodium-containing polyanionic compound or a Prussian blue analogue.

[0105] In this paper, the term "polyanionic compound" refers to a group of compounds with a three-dimensional network structure formed by strong covalent bonds connecting tetrahedral and polyhedral anionic structural units.

[0106] In some embodiments, the polyanionic compound includes compounds with the general formula Na. b Me c (PO4) dsodium-containing phosphate of O2X, wherein A is one or more of H, Li, Na, K and NH4, Me is one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X is one or more of F, Cl and Br, 0<b≤4, 0<c≤2, 1≤d≤3.

[0107] As used herein, the term "Prussian blue analogue" refers to a class of compounds constructed based on the structural principle of Prussian blue, which are synthesized by replacing central metal ions or changing ligands to obtain different compounds with similar framework structures.

[0108] In some embodiments, the Prussian blue analogue includes a compound of the general formula Na x P[R(CN)6] δ ·zH2O, wherein P and R are each independently selected from at least one of transition metal elements, 0<x≤2, 0<δ≤1, and 0≤z≤10.

[0109] In some embodiments, the battery cell includes a zinc-ion battery, and the matrix includes a manganese-based compound and a vanadium-based compound.

[0110] In some embodiments, the manganese-based compound includes one or more of MnO2, Mn2O3, Mn3O4, and spinel-phase ZnMn2O4.

[0111] In some embodiments, the vanadium-based compound includes one or more of vanadium oxides and vanadium-based polyanionic frameworks.

[0112] Compared to oil-based cathode slurries, using aqueous cathode slurries to prepare battery cells is advantageous in reducing costs and environmental pollution. It also avoids the impact of residual oily solvents (e.g., N-methylpyrrolidone) in the film layer on electrochemical performance, which is a consequence of using oil-based cathode slurries. However, battery cells prepared using aqueous cathode slurries face the challenge of low initial charge-discharge specific capacity of the cathode active material. Analysis suggests this may be because during the preparation of aqueous cathode slurries, active ions (e.g., lithium ions) in the cathode active material matrix (e.g., lithium transition metal phosphates) undergo a displacement reaction with hydrogen ions, leading to their dissolution and irreversible loss, thus causing a deterioration in the initial charge-discharge specific capacity. Therefore, the positive electrode active material of the battery cell in this application includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. This coating layer helps to reduce the contact between the positive electrode active material matrix and water during the preparation of the aqueous positive electrode slurry, thereby reducing the displacement reaction between active ions and hydrogen ions in the matrix, reducing the dissolution of active ions, and thus improving the initial charge-discharge specific capacity of the positive electrode active material. Furthermore, compared to the method of adding a lithium replenishing agent to the positive electrode sheet to compensate for the loss of active ions (e.g., lithium ions) and thus improve the initial charge-discharge specific capacity, the positive electrode active material of this application reduces the dissolution of active ions, thereby reducing the damage to the matrix structure and helping to improve the structural stability of the matrix, thus also improving the cycle stability of the battery cell. Moreover, the phthalocyanine complex is stable, non-toxic, and inexpensive, and can promote charge transfer, making the coating layer help to increase the active ion transport channels, increase the active ion diffusion rate, and thus improve the electrochemical stability of the positive electrode active material, which is beneficial to further improving the cycle stability of the battery cell.

[0113] In some embodiments, the matrix is ​​selected from lithium-containing transition metal phosphates.

[0114] Lithium-containing transition metal phosphates are suitable for the preparation of aqueous cathode slurries, which is beneficial for further improving the cycle stability of battery cells prepared from aqueous cathode slurries.

[0115] In some implementations, the I of the positive electrode film D / I G It is 0.5-1.55, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

[0116] I D / I GThe magnitude of the ratio reflects information about the defect density and graphitization degree in the material. A larger ratio means a higher proportion of defects or amorphous carbon structures relative to ordered graphite or graphene structures in the sample, indicating a lower degree of graphitization and more abundant defects. Conversely, a smaller ratio indicates a lower degree of graphitization and more abundant defects. D / I G A smaller ratio indicates that the material is relatively pure, has fewer defects, and a higher degree of graphitization.

[0117] In this paper, the I of the positive electrode film D / I G Measurements can be performed using methods and equipment known in the art. As an example, referring to GB / T 40219-2021, a LabRAM HR Evolution laser micro Raman spectrometer was used for testing. A solid-state laser with a wavelength of 523 nm was used as the light source, with a beam diameter of 1.2 μm and a power of 1 mW. One hundred points were sampled in a 100 μm × 100 μm area, and the wavelength at each point was calculated at 1350 ± 100 cm⁻¹. -1 Peak intensity I D With 1580±100cm -1 Peak intensity I G I D / I G The ratio, taking 100 points of I D / I G The median value is used as the I of the positive electrode film. D / I G The details are as follows:

[0118] (1) Sample preparation: Disassemble the battery cell to obtain the positive electrode sheet, scrape off the positive electrode film layer, grind it to make a test sample, and apply the sample to a glass slide; (2) Sample focusing: Adjust the platform height, adjust the objective lens, and focus the sample particles through coarse adjustment, fine adjustment and trackball operation; (3) Create a new scan: including parameter settings and selection of storage path, etc.; (4) Run the scan: Run the scan according to the set parameters (wavenumber range: 3200~100cm). -1 ).

[0119] In some implementations, the I of the positive electrode film D / I G It can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.55, or a range of any two of the above values, or other unlisted values ​​within the range.

[0120] I of the positive electrode film D / I GWithin the aforementioned range, it is evident that the outer side of the core of the positive electrode active material is successfully coated with a coating layer including phthalocyanine complexes, which helps to improve the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0121] In some implementations, the kernel's I D / I G It ranges from 0.7 to 1.3.

[0122] kernel I D / I G It can be achieved through the I of the core of the positive electrode film described above. D / I G Test using a similar method.

[0123] In some implementations, the kernel's I D / I G It can be 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, or a range of any two of the above values, or other unlisted values ​​within the range.

[0124] In some implementations, the phthalocyanine complex accounts for 0.1%-2% of the total mass of the positive electrode active material.

[0125] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, or a range of any two of the above values, or other unlisted values ​​within the range.

[0126] Based on the total mass of the positive electrode active material, when the mass ratio of phthalocyanine complex is within the above range, it helps to improve the cycle stability of the battery cell while the positive electrode active material also has a better initial charge-discharge capacity.

[0127] In some implementations, the kernel's I D / I G The mass percentage of phthalocyanine complexes is 0.1%-0.4% based on the total mass of the positive electrode active material, ranging from 0.7% to 1.0%.

[0128] In some implementations, the kernel's I D / I G The range is 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or any two of the above values, or any other unlisted value within the range.

[0129] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, or a range of any two of the above values, or other unlisted values ​​within the range of the above values.

[0130] When the I of the core of the positive electrode active material D / I G When the value is 0.7-1.0, it indicates that the graphitization degree of the core surface is relatively high, the coating integrity of the carbon coating layer is good, and the contact area between the core and the aqueous solvent is small. This reduces the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions. Therefore, when the mass ratio of phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, the cycle stability of the battery cell can be improved, and the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0131] In some implementations, the kernel's I D / I G The mass percentage of phthalocyanine complexes is 0.5%-2% based on the total mass of the positive electrode active material, ranging from 1.0 to 1.3.

[0132] In some implementations, the kernel's I D / I G It can be 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, or a range consisting of any two of the above values, or any other unlisted value within the range.

[0133] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or a range of any two of the above values, or other unlisted values ​​within the range.

[0134] When the kernel's I D / I G When the value is 1.0-1.3, it indicates that the graphitization degree of the core surface is low, the integrity of the carbon coating layer is poor, and the contact area between the core and the aqueous solvent is large. As a result, the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions is high. Therefore, when the mass ratio of phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, it helps to improve the cycle stability of the battery cell. At the same time, the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0135] In some embodiments, the phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, or manganese phthalocyanine.

[0136] In some embodiments, the phthalocyanine complex includes copper phthalocyanine.

[0137] Copper phthalocyanine has a simple preparation method and a suitable cost, making it suitable for the industrial preparation of the battery cells of this application.

[0138] In some embodiments, the thickness of the coating layer is 150nm-500nm, and optionally 200nm-400nm.

[0139] In this paper, the thickness of the coating layer can be measured using methods and equipment known in the art. As an example, the positive electrode sheet of the battery in its initial state or after cycling is disassembled, the positive electrode film layer of the positive electrode sheet is peeled off, the positive electrode film layer is thoroughly washed with acetone to remove binders and dispersants, etc., and then filtered and dried to obtain positive electrode active material powder. The phthalocyanine complex coated on the surface of lithium iron phosphate can be observed by ion polishing cross-sectional morphology analysis, combined with scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the thickness of the coating layer is measured. The arithmetic mean of the test results of 10 TEM images is taken as the average thickness of the coating layer.

[0140] In some embodiments, the thickness of the coating layer can be 150nm, 200nm, 250nm, 30nm, 350nm, 400nm, 450nm, 500nm, or a range of any two of the above thicknesses, or a value within the range.

[0141] When the thickness of the coating layer is within the above range, it helps to further improve the cycle stability of the battery cell. At the same time, the positive electrode active material has excellent initial charge and discharge specific capacity and kinetic performance, which helps to alleviate polarization and comprehensively improve the electrochemical performance of the battery.

[0142] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material is 0.5 μm-5 μm.

[0143] In some embodiments, the volume distribution particle size Dv99 of the positive electrode active material is 10 μm-15 μm.

[0144] In this paper, the terms "Dv50" and "Dv99" refer to the particle size corresponding to a cumulative volumetric particle size distribution percentage of 50% and 99%, respectively.

[0145] In this paper, the volumetric particle size distribution of the positive electrode active material can be measured using methods and equipment known in the art. As an example, a battery cell is disassembled to obtain the positive electrode sheet. The positive electrode film is peeled off, thoroughly washed with acetone to remove the binder, and dried to obtain powder for subsequent characterization testing. An appropriate amount of the powder to be tested is taken and determined using a laser particle size analyzer according to GB / T 19077-2016. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0146] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, or a range of any two of the above values, or a value within the range.

[0147] In some embodiments, the volume distribution particle size Dv99 of the positive electrode active material can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range of any two of the above values, or a value within the range.

[0148] In some embodiments, the positive electrode film layer further includes a binder, which includes one or more of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

[0149] In some embodiments, methylcellulose and its salts include one or more of lithium methylcellulose, sodium methylcellulose, and potassium methylcellulose.

[0150] In some embodiments, alginate and its salts include one or more of lithium alginate, sodium alginate, and potassium alginate.

[0151] The aforementioned binder helps to enhance the adhesion between the positive electrode film layer formed by the aqueous positive electrode slurry and the current collector, thereby helping to further improve the cycle stability of the battery cell.

[0152] In some embodiments, the lithium-containing transition metal phosphate includes components having the following general formula:

[0153] Li m A a Fe x D d P y E e O z G g ,

[0154] The A element comprises at least one element selected from Al, Na, K, or Mg; the D element comprises at least one element selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti, or V; the E element comprises at least one element selected from B, S, Si, or N; the G element comprises at least one element selected from S, F, Cl, or Br; the m element is selected from the range of 0.5 to 1.15; the a element is selected from the range of 0 to 0.1; the x element is selected from the range of 0.5 to 1; the d element is selected from the range of 0 to 0.5; the y element is selected from the range of 0.5 to 1; the e element is selected from the range of 0 to 0.5; the z element is selected from the range of 3.5 to 4; and the g element is selected from the range of 0 to 0.5.

[0155] When used herein, "lithium phosphates include components having the following general formula" is not limited to substances represented by the general molecular formula, but also includes other substances formed by further appropriate modifications based on the general molecular formula, which are not limited herein. The use of "general formula" is for ease of description only and is not intended to limit this application. It is understood that new materials or substances obtained by appropriate modifications based on the listed positive electrode active materials are also within the scope of positive electrode active materials. The aforementioned appropriate modifications refer to acceptable modification methods for positive electrode active materials, and non-limiting examples include coating modification.

[0156] In some implementations, m can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, or a range of any two m values, or a value within that range.

[0157] In some implementations, 'a' can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range consisting of any two of the above 'a's, or a value within that range.

[0158] In some implementations, x can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or a range of any two x values ​​or a value within that range.

[0159] In some implementations, d can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or a range of any two d values, or a value within that range.

[0160] In some implementations, y can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or a range of any two of the above y values, or a value within that range.

[0161] In some implementations, e can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or a range consisting of any two of the above e, or a value within that range.

[0162] In some implementations, z can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, or a range consisting of any two of the above z, or a value within the range.

[0163] In some implementations, g can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or a range of any two g values, or a value within that range.

[0164] [Preparation methods for battery cells]

[0165] This application also provides a method for preparing a single battery cell, the method comprising at least the following steps:

[0166] A positive electrode active material is obtained, the positive electrode active material comprising a core and a coating layer covering at least a portion of the surface of the core, the coating layer comprising a phthalocyanine complex;

[0167] A mixture including positive electrode active material and water is obtained to obtain an aqueous positive electrode slurry;

[0168] Battery cells are prepared using aqueous cathode slurry;

[0169] The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

[0170] Compared to oil-based cathode slurries, using aqueous cathode slurries to prepare battery cells is advantageous in reducing costs and environmental pollution. It also avoids the impact of residual oily solvents (e.g., N-methylpyrrolidone) in the film layer on electrochemical performance, which is a consequence of using oil-based cathode slurries. However, battery cells prepared using aqueous cathode slurries face the challenge of low initial charge-discharge specific capacity of the cathode active material. Analysis suggests this may be because during the preparation of aqueous cathode slurries, active ions (e.g., lithium ions) in the cathode active material matrix (e.g., lithium transition metal phosphates) undergo a displacement reaction with hydrogen ions, leading to their dissolution and irreversible loss, thus causing a deterioration in the initial charge-discharge specific capacity.

[0171] Phthalocyanine complexes possess an 18π-electron conjugated structure, exhibiting strong coordination ability and redox properties. This allows the six-membered rings of the phthalocyanine complex to undergo π-π stacking within themselves. Furthermore, the phthalocyanine complex itself contains multiple six-membered rings, which can continue to stack π-π with the six-membered rings of the carbon coating layer on the substrate surface, thereby achieving stable coating of the core of the positive electrode active material. The battery cell preparation method of this application utilizes the aforementioned positive electrode active material, which helps to reduce the contact between active ions and water in the positive electrode active material matrix during the preparation of aqueous positive electrode slurry, thereby reducing the displacement reaction between the matrix and hydrogen ions, reducing the dissolution of active ions, and thus improving the initial charge-discharge specific capacity of the positive electrode active material. Compared to the method of adding lithium replenishing agents to the positive electrode sheet to compensate for the loss of active ions (e.g., lithium ions) and thus improve the initial charge-discharge specific capacity, the positive electrode active material of this application reduces the dissolution of active ions, thereby reducing the damage to the matrix structure and helping to improve the structural stability of the matrix, thus also improving the cycle stability of the battery cell. Furthermore, phthalocyanine complexes are stable, non-toxic, and inexpensive, and can promote charge transfer. This allows the coating layer containing phthalocyanine complexes to increase the active ion transport channels and improve the active ion diffusion rate, thereby enhancing the electrochemical stability of the positive electrode active material and further improving the cycle stability of the battery cell.

[0172] In some embodiments, the matrix is ​​selected from lithium-containing transition metal phosphates.

[0173] Lithium-containing transition metal phosphates are suitable for the preparation of aqueous cathode slurries, which is beneficial for further improving the cycle stability of battery cells prepared from aqueous cathode slurries.

[0174] In some embodiments, obtaining the positive electrode active material includes:

[0175] Positive electrode active materials are obtained by treating the core and phthalocyanine complex using one or more of the following processes: dry mixing, ultrasonic processing, magnetron sputtering, dot coating, and dip coating.

[0176] All of the above processes can achieve stable coating of the core by phthalocyanine complexes, thereby reducing the irreversible loss of active ions and the damage to the matrix structure during the preparation of aqueous cathode slurry, and thus improving the initial charge-discharge specific capacity of the cathode active material and the cycle stability of the battery.

[0177] In some embodiments, the preparation method includes at least the following steps:

[0178] The core and phthalocyanine complex are dry-mixed to obtain the positive electrode active material;

[0179] A mixture comprising positive electrode active material and water is obtained to produce an aqueous positive electrode slurry.

[0180] Using a dry mixing process helps to further improve the coating stability of phthalocyanine complexes on the core. The dry mixing process can also reduce damage to the matrix structure, control the coating amount of phthalocyanine complexes to a moderate level, and thus further improve the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery. Furthermore, the dry mixing process is suitable for industrial applications.

[0181] In some implementations, the kernel's I D / I G It is 0.7-1.3, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

[0182] In some implementations, the kernel's I D / I G It can be 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, or a range of any two of the above values, or other unlisted values ​​within the range.

[0183] In some implementations, the phthalocyanine complex accounts for 0.1%-2% of the total mass of the positive electrode active material.

[0184] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, or a range of any two of the above values, or other unlisted values ​​within the range.

[0185] Based on the total mass of the positive electrode active material, when the mass ratio of phthalocyanine complex is within the above range, it helps to improve the cycle stability of the battery cell while the positive electrode active material also has a better initial charge-discharge capacity.

[0186] In some implementations, the kernel's I D / I G The mass percentage of phthalocyanine complexes is 0.1%-0.4% based on the total mass of the positive electrode active material, ranging from 0.7% to 1.0%.

[0187] In some implementations, the kernel's I D / I GThe range is 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or any two of the above values, or any other unlisted value within the range.

[0188] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, or a range of any two of the above values, or other unlisted values ​​within the range of the above values.

[0189] When the I of the core of the positive electrode active material D / I G When the value is 0.7-1.0, it indicates that the graphitization degree of the core surface is relatively high, the coating integrity of the carbon coating layer is good, and the contact area between the core and the aqueous solvent is small. This reduces the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions. Therefore, when the mass ratio of phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, the cycle stability of the battery cell can be improved, and the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0190] In some implementations, the kernel's I D / I G The mass percentage of phthalocyanine complexes is 0.5%-2% based on the total mass of the positive electrode active material, ranging from 1.0 to 1.3.

[0191] In some implementations, the kernel's I D / I G It can be 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, or a range consisting of any two of the above values, or any other unlisted value within the range.

[0192] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or a range of any two of the above values, or other unlisted values ​​within the range.

[0193] When the kernel's I D / I GWhen the value is 1.0-1.3, it indicates that the graphitization degree of the core surface is low, the integrity of the carbon coating layer is poor, and the contact area between the core and the aqueous solvent is large. As a result, the probability of active ions dissolving due to the displacement reaction between active ions and hydrogen ions is high. Therefore, when the mass ratio of phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, it helps to improve the cycle stability of the battery cell. At the same time, the positive electrode active material also has excellent initial charge and discharge specific capacity.

[0194] In some embodiments, the phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, and manganese phthalocyanine.

[0195] In some embodiments, the particle size of the phthalocyanine complex is 200 nm to 600 nm.

[0196] In some embodiments, the particle size of the phthalocyanine complex is 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, or a range of any two of the above values, or other unlisted values ​​within the range.

[0197] The particle size of phthalocyanine complexes within the above range is beneficial for achieving stable coating of the core, while also having low preparation cost.

[0198] In some embodiments, the preparation method includes at least the following steps:

[0199] The core and phthalocyanine complex are dry-mixed to obtain the positive electrode active material;

[0200] A mixture comprising positive electrode active material, water, and binder is obtained to produce an aqueous positive electrode slurry.

[0201] Dry mixing the core and phthalocyanine complex, followed by mixing with water and binder, helps to further reduce the displacement reaction between active ions and hydrogen ions in the positive electrode active material matrix, further reducing the dissolution of active ions and damage to the matrix structure, thereby further improving the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0202] In some embodiments, the binder includes one or more of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

[0203] The aforementioned binder helps to enhance the adhesion between the positive electrode film layer formed by the aqueous positive electrode slurry and the current collector, thereby helping to further improve the cycle stability of the battery cell.

[0204] In some embodiments, the mixture also includes one or more of a conductive agent and a dispersant.

[0205] In some embodiments, the preparation method includes at least the following steps:

[0206] The core and phthalocyanine complex are first dry-mixed to obtain the positive electrode active material;

[0207] The positive electrode active material and the conductive agent are dry-mixed a second time to obtain a first mixture;

[0208] The first mixture, the dispersant, and water are first mixed to obtain the second mixture;

[0209] The second mixture and the binder are mixed a second time to obtain a mixture, which yields an aqueous positive electrode slurry.

[0210] The above preparation process helps to improve the coating stability of the core by the phthalocyanine complex, uniformly mix the positive electrode active material, conductive agent, dispersant and binder, thereby realizing the role of conductive agent, dispersant and binder, and further improving the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0211] In some embodiments, the rotational speed of the first dry mixing is 300 r / min-1500 r / min, and can be selected as 500 r / min-800 r / min.

[0212] In some embodiments, the rotational speed of the first dry mix can be 300 r / min, 500 r / min, 700 r / min, 900 r / min, 1100 r / min, 1300 r / min, 1500 r / min, or a range of any two of the above rotational speeds, or other unlisted values ​​within the range.

[0213] In some embodiments, the rotational speed of the second dry mixer is 300 r / min-1500 r / min, and can be selected as 500 r / min-800 r / min.

[0214] In some embodiments, the rotational speed of the second dry mix can be 300 r / min, 500 r / min, 700 r / min, 900 r / min, 1100 r / min, 1300 r / min, 1500 r / min, or a range of any two of the above rotational speeds, or other unlisted values ​​within the range.

[0215] In some embodiments, the rotational speed of the first mixing is 200 r / min-1800 r / min, optionally 800 r / min-1200 r / min.

[0216] In some embodiments, the rotational speed of the first mixing may be 200 r / min, 400 r / min, 600 r / min, 800 r / min, 1000 r / min, 1200 r / min, 1400 r / min, 1600 r / min, 1800 r / min, or a range of any two of the above rotational speeds, or other unlisted values ​​within the range.

[0217] In some embodiments, the rotational speed of the second mixing is 200 r / min-1800 r / min, optionally 800 r / min-1200 r / min.

[0218] In some embodiments, the rotational speed of the second mixing may be 200 r / min, 400 r / min, 600 r / min, 800 r / min, 1000 r / min, 1200 r / min, 1400 r / min, 1600 r / min, 1800 r / min, or a range of any two of the above rotational speeds, or other unlisted values ​​within the range.

[0219] The aforementioned rotational speed helps to balance the coating stability of the phthalocyanine complex on the core and the structural integrity of the core, uniformly mix the positive electrode active material, conductive agent, dispersant and binder, thereby realizing the functions of the conductive agent, dispersant and binder, and further improving the initial charge and discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0220] In some embodiments, the solid content of the aqueous cathode slurry is 50%-70%; and / or,

[0221] The viscosity of the aqueous cathode slurry is 3000 mPa·s-9000 mPa·s.

[0222] In this application, the term "viscosity" is a measure of the viscosity of a fluid, representing the fluid dynamics and the internal frictional phenomena.

[0223] In this paper, the viscosity of aqueous cathode slurry can be measured using methods and equipment known in the art. For example, the viscosity of the prepared aqueous cathode slurry can be tested using a digital viscometer, referring to the national standard GB / T10247-2008 "Viscosity Measurement Method". At a certain temperature, when the rotor rotates continuously at a constant speed in the sample, the shear force it experiences causes the spring to generate torque. The torque is proportional to the viscosity, and the viscosity value is obtained.

[0224] In some embodiments, the solid content of the aqueous cathode slurry can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, or a range of any two of the above solid contents, or other unlisted values ​​within the range of contents.

[0225] In some embodiments, the viscosity of the aqueous cathode slurry can be 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, or a range of any two of the above viscosities, or other unlisted values ​​within the range of the above viscosities.

[0226] When the solid content of the aqueous cathode slurry is within the above range, the aqueous cathode slurry has excellent stability and dispersibility, the slurry is not prone to sedimentation, and it has excellent coating performance, which is conducive to the spreading of the slurry.

[0227] When the viscosity of the aqueous cathode slurry is within the above range, the aqueous cathode slurry has excellent stability and dispersibility, excellent coating performance, suitable drying time after coating, and uniform electrode stress, making it less prone to cracking.

[0228] [Positive electrode plate]

[0229] This application provides a positive electrode sheet, including a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes a positive electrode active material, a binder, and a conductive agent. The positive electrode active material includes the positive electrode active material of any embodiment of this application or the positive electrode active material prepared by the preparation method of any embodiment of this application.

[0230] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0231] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0232] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0233] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in solvent water to form an aqueous positive electrode slurry; coating the aqueous positive electrode slurry onto the positive current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0234] [Negative electrode plate]

[0235] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0236] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0237] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0238] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0239] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0240] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0241] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0242] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0243] [Electrolytes]

[0244] The electrolyte acts as a conductor of ions between the positive and negative electrode plates. This application does not specifically limit the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, solid, or gel-like.

[0245] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0246] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0247] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0248] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0249] [Isolation membrane]

[0250] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0251] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0252] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0253] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0254] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0255] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 3 The example shown is a square-structured battery cell 5.

[0256] In some implementations, refer to Figure 4 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.

[0257] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0258] Figure 5 This is battery module 4, used as an example. (See reference...) Figure 5In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0259] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0260] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0261] Figure 6 and Figure 7 This is battery pack 1 as an example. (See reference...) Figure 6 and Figure 7 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0262] In addition, this application also provides a battery device, including the battery cell provided in the first aspect of this application, wherein the battery device includes at least one of a battery module, a battery pack, and an energy storage battery.

[0263] In addition, this application also provides an electrical device, which includes the battery cell provided in the first aspect of this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0264] As the electrical device, a single battery cell, a battery module, or a battery pack can be selected according to its usage requirements.

[0265] Figure 8 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of individual battery cells, a battery pack or battery module can be used.

[0266] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0267] Example

[0268] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0269] Preparation method

[0270] Example 1

[0271] 1) Preparation of copper phthalocyanine

[0272] S1: By weight, mix 280 parts nitrobenzene, 56 parts phthalonitrile, 13 parts urea, 0.6 parts ammonium molybdate, and 11 parts cuprous chloride evenly on an ultrasonic generator; the ultrasonic conditions are 80 Hz and the time is 30 min.

[0273] S2: Place the uniformly mixed materials in a microwave reactor and heat to 180°C. The materials react and the temperature is maintained for 20 minutes. The reaction ends and the initial product is obtained.

[0274] S3: Remove the preliminary product and cool it at 0-10℃. Then add water at pH 12 and 90℃, stir, wash, and allow to separate into layers. Take the lower layer. Repeat this process until the pH of the lower layer is 7. Then perform azeotropic distillation on the lower layer to remove residual polar organic solvents and water, obtaining a filter cake. Wash the product with methanol and dry it to obtain nano-sized copper phthalocyanine with an average particle size of 400nm and the following structural formula:

[0275]

[0276] 2) Preparation of positive electrode sheet

[0277] S1: By weight, 960 parts of lithium iron phosphate and 3 parts of nano-sized copper phthalocyanine (C 32 H 16 CuN8) was mixed using a dual planetary stirrer at 700 r / min for 10 min. The lithium iron phosphate comprises a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The lithium iron phosphate has an I D / I G It is 0.81;

[0278] S2: The dry mixture obtained in S1 is mixed with 7 parts of conductive carbon black (Super P) and stirred in a double planetary mixer at a speed of 700 r / min for 10 min.

[0279] S3: Add 30 parts of polyether phosphate polymer (purchased from Shenzhen Haofei New Materials Co., Ltd., brand name: HFF-2903) and water to the dry mixture obtained in S2, and stir at 1000r / min for 40min with a double planetary mixer to obtain a lumpy material;

[0280] S4: Add 30 parts of water-based binder (acrylonitrile-acrylic acid copolymer and polyethyleneimine compound, ratio 2:1, molecular weight of acrylonitrile-acrylic acid copolymer 300,000-2,000,000, molecular weight of polyethyleneimine 2,000-70,000, purchased from Shenzhen Yanyi New Materials Co., Ltd.) and stir the agglomerated material obtained in S3 at 1000 r / min for 30 min with dual planetary stirring to obtain an aqueous positive electrode slurry. The solid content of the slurry is 60% and the viscosity is 5000 mPa.

[0281] S5: Apply the aqueous cathode slurry at a concentration of 120g / m 2 The coating is evenly applied to the positive current collector, and then placed in a vacuum oven at 90 degrees Celsius for 4 hours. Afterwards, cold pressing and slitting processes are performed to obtain the aqueous positive electrode sheet.

[0282] 3) Preparation of negative electrode sheet

[0283] Artificial graphite, conductive carbon black (Super P), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in water at a ratio of 96.2:0.8:0.8:1.2 to obtain a negative electrode slurry, with a concentration of 245 g / m³. 2 The coating is applied to both sides of the copper foil, and after cold pressing and cutting, the negative electrode sheet is obtained.

[0284] 4) Preparation of the diaphragm

[0285] A polyethylene film with a thickness of 13 μm was used as the separator.

[0286] 5) Preparation of electrolyte

[0287] Ethylene carbonate, diethyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 1:1:1. LiPF6 was then dissolved in this solution to obtain an electrolyte. The concentration of LiPF6 in this electrolyte was 1 mol / L.

[0288] 6) Battery assembly

[0289] The electrodes are arranged in the order of "separator-negative electrode-separator-positive electrode". One end of the positive electrode, negative electrode, and two separators is fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. The winding shaft is rotated by a motor to wind the positive electrode, negative electrode, and two separators to obtain a bare cell. The bare cell is then welded with tabs and placed in an aluminum shell. It is then baked in a vacuum oven at 100°C for 8 hours. The electrolyte prepared above is injected into the dried cell. After encapsulation, settling, formation, shaping, and capacity testing, the battery cell of Example 1 is obtained.

[0290] Examples 2-7

[0291] The battery cells in Examples 2-7 are prepared using methods similar to those in Example 1, the difference being the change in the I0 of lithium iron phosphate. D / I G The amounts of copper phthalocyanine and / or added are detailed in Table 1.

[0292] Examples 8-10

[0293] The battery cells of Examples 8-10 are prepared in a similar manner to the battery cells of Example 1, except that the type of phthalocyanine complex is changed, as detailed in Table 1.

[0294] Example 11

[0295] The battery cell of Example 11 is prepared in a similar manner to the battery cell of Example 1, except that in Example 11, at least a portion of the surface of the lithium iron phosphate is coated with a phthalocyanine complex using an ultrasonic process, as detailed below:

[0296] By weight, 960 parts of lithium iron phosphate and 3 parts of nano-sized copper phthalocyanine (C) were mixed. 32 H 16 CuN8) was stirred and mixed evenly on an ultrasonic generator at a frequency of 40 kHz for 30 min.

[0297] Example 12

[0298] The battery cell of Example 12 is prepared in a similar way to the battery cell of Example 1, except that the type of binder is changed. The binder is CMC (carboxymethyl cellulose), as shown in Table 1.

[0299] Example 13

[0300] The battery cell in Example 13 is prepared using a similar method to the battery cell in Example 1, except that the preparation process of the aqueous cathode slurry is changed, as detailed below:

[0301] By weight, 960 parts of lithium iron phosphate, 3 parts of nano-grade copper phthalocyanine, 7 parts of conductive carbon black (Super P), dispersant polyether phosphate polymer (purchased from Shenzhen Haofei New Materials Co., Ltd., brand: HFF-2903), and water-based binder were mixed by a double planetary mixer at a speed of 700 r / min for 30 min to obtain a dry mixture. Water was then added and the mixture was stirred by a double planetary mixer at 1000 r / min for 40 min to obtain an aqueous positive electrode slurry. The solid content of the slurry was 60%, and the viscosity was 5500 mPa·s.

[0302] Comparative Example 1

[0303] The preparation method of the battery cell in Comparative Example 1 is similar to that of the battery cell in Example 3, except that no phthalocyanine complex was added during the preparation of the aqueous positive electrode sheet, as detailed in the table.

[0304] Comparative Example 2

[0305] The battery cell of Comparative Example 2 was prepared in a similar manner to the battery cell of Example 3, except that no phthalocyanine complex was added during the preparation of the aqueous positive electrode, and 0.31% of lithium supplementer LiNiO2 was added.

[0306] Comparative Example 3

[0307] The battery cell of Comparative Example 3 was prepared using a similar method to the battery cell of Example 1, except that lithium iron phosphate was replaced with ternary material LiNi. 0.33 Mn 0.33 Co 0.33 O2.

[0308] Comparative Example 4

[0309] The battery cell of Comparative Example 4 was prepared in a similar manner to the battery cell of Example 3, except that the phthalocyanine complex was replaced with copper octahydroxyphthalocyanine.

[0310] II. Performance Testing

[0311] 1. Positive electrode film, lithium iron phosphate I D / I G test

[0312] According to GB / T 40219-2021, a LabRAM HR Evolution laser micro Raman spectrometer was used for testing. A solid-state laser with a wavelength of 523 nm was used as the light source, with a beam diameter of 1.2 μm and a power of 1 mW. One hundred points were sampled in a 100 μm × 100 μm region, and the wavelength of each point at 1350 ± 100 cm⁻¹ was calculated. -1 Peak intensity I D With 1580±100cm -1 Peak intensity IG I D / I G The ratio, taking 100 points of I D / I G The median value is used as the I value for the positive electrode or lithium iron phosphate. D / I G .

[0313] 2. Testing of the coating layer and thickness of the positive electrode active material.

[0314] Disassemble the positive electrode sheet of the battery in its initial state or after cycling, peel off the positive electrode film layer, thoroughly wash the positive electrode film layer with acetone to remove binders and dispersants, filter and dry to obtain positive electrode active material powder. Ion polishing cross-sectional morphology analysis, combined with scanning electron microscopy (SEM) and transmission electron microscopy (TEM), allows observation of the coating layer on the surface of lithium iron phosphate, and the thickness of the coating layer can be measured. X-ray energy dispersive spectroscopy (EDS) is then performed for surface scanning (the surface scanning elements are selected according to the elements to be measured) to obtain the corresponding mapping spectrum, which can measure the average thickness of the positive electrode active material surface, including phthalocyanine complexes and the coating layer. Figure 1 , Figure 2 As shown, the test results show that the surface of the positive electrode active material in Example 1 has a coating layer, which includes copper and has a thickness of 300 nm.

[0315] 3. Particle size testing of positive electrode active materials

[0316] The battery cell was disassembled to obtain the positive electrode sheet. The positive electrode film was peeled off, and the electrode was thoroughly washed with acetone to remove the binder. The powder was then dried for subsequent characterization testing. An appropriate amount of the powder was taken and measured using a laser particle size analyzer according to GB / T 19077-2016. The testing instrument could be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0317] 4. Testing of initial charge / discharge specific capacity and cycle capacity retention of positive electrode active materials.

[0318] At 25°C, the prepared battery cell is charged to 3.65V with a constant current of 1 / 3C, and then charged to 0.05C with a constant voltage of 3.65V. The resulting charge is the initial charge. After standing for 5 minutes, it is discharged to 2V with a constant current of 1 / 3C. The resulting discharge capacity is the initial capacity of the cell.

[0319] For Comparative Example 3, which uses ternary materials as the positive electrode active material, the battery is charged at a constant current of 1 / 3C to 4.5V, and then charged at a constant voltage of 4.5V to a current of 0.05C. The resulting charge is the initial charge. After standing for 5 minutes, the battery is discharged at a constant current of 1 / 3C to 2.5V. The resulting discharge capacity is the initial capacity of the cell.

[0320] Therefore, the initial charge capacity = initial charge amount / mass of positive electrode active material;

[0321] Initial discharge capacity = initial capacity / mass of positive electrode active material.

[0322] The prepared battery cells were subjected to cyclic charge-discharge tests according to the above method, and the discharge capacity after each cycle was recorded. The capacity retention rate after 500 cycles was calculated as (discharge capacity after the 500th cycle / initial capacity) * 100%.

[0323] 5. Test methods for distinguishing between oil-based and water-based electrode sheets

[0324] The battery cell was disassembled, the positive electrode was separated, and cut into 5cm*5cm electrode sheets. The electrode sheets were placed in NMP. After 1 hour, the oil-based electrode film area completely fell off, leaving only the current collector foil, while the water-based electrode film area did not fall off.

[0325] III. Analysis of Test Results for Each Embodiment and Comparative Example

[0326] Secondary batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.

[0327] Table 1

[0328]

[0329] Table 2

[0330]

[0331] Examples 1-13 provide a single battery cell, comprising a positive electrode sheet, which includes a positive current collector and a positive electrode film layer disposed on at least one side of the current collector. The positive electrode film layer includes a positive electrode active material, and the positive electrode sheet is an aqueous electrode sheet. The positive electrode active material includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof. The positive electrode active material exhibits excellent initial charge-discharge specific capacity, and the battery cell exhibits excellent cycle stability.

[0332] As can be seen from the comparison between Examples 1-13 and Comparative Example 1, the battery cells of this application use aqueous positive electrode slurry to prepare positive electrode sheets, which reduces costs and environmental pollution. At the same time, the positive electrode active material includes a core and a coating layer covering at least part of the surface of the core. The coating layer includes phthalocyanine complexes, which helps to improve the initial specific capacity of the positive electrode active material and improve the cycle stability of the battery cell.

[0333] As can be seen from the comparison between Examples 1-13 and Comparative Example 2, the battery cells of this application use aqueous positive electrode slurry to prepare positive electrode sheets, which reduces costs and environmental pollution. Compared with adding lithium supplementation agents to the positive electrode sheets, the use of a positive electrode active material including a core and a coating layer covering at least part of the surface of the core, and the coating layer including phthalocyanine complexes, improves the initial charge and discharge specific capacity of the positive electrode active material and further improves the cycle stability of the battery.

[0334] As can be seen from the comparison between Examples 1-13 and Comparative Example 3, the positive electrode active material matrix selected from lithium transition metal phosphates is more suitable for the preparation of aqueous positive electrode sheets, and the battery's initial efficiency and cycle stability are further improved. Although lithium transition metal oxides have a higher theoretical specific capacity, their strong reactivity with water leads to severe side reactions when used to prepare aqueous positive electrode slurries, resulting in structural damage and significantly deteriorating the specific capacity of the positive electrode active material and the battery's cycle stability.

[0335] As can be seen from the comparison between Examples 1-13 and Comparative Example 4, the phthalocyanine complex in the coating layer of the positive electrode active material in this application embodiment does not have grafting groups, which is more conducive to achieving coating and improving the stability of the SEI film (solid electrolyte interface film) during subsequent battery cycles, thereby improving the initial specific capacity of the positive electrode active material, as well as the battery's first-cycle efficiency and cycle stability. In contrast, the octahydroxy phthalocyanine copper used in Comparative Example 4 has hygroscopic grafting groups, which is not conducive to reducing the dissolution of active ions and the stability of the SEI film. Therefore, the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery are poor.

[0336] As can be seen from Examples 1-5, the kernel's I D / I G With a mass ratio of 0.7-1.0, based on the total mass of the positive electrode active material, when the mass percentage of phthalocyanine complex is 0.1%-0.4%, the battery cell exhibits excellent first-efficiency performance and cycle stability, while the positive electrode active material also exhibits excellent initial specific capacity.

[0337] As can be seen from Examples 6-7, the kernel's I D / I GWith a mass ratio of 1.0-1.3, based on the total mass of the positive electrode active material, when the mass percentage of phthalocyanine complex is 0.5%-2%, the battery cell exhibits excellent first-efficiency performance and cycle stability, while the positive electrode active material also exhibits excellent initial specific capacity.

[0338] As can be seen from the comparison between Example 3 and Example 6, when the kernel's I D / I G With a mass ratio of 1.0-1.3, based on the total mass of the positive electrode active material, when the mass percentage of phthalocyanine complex is 0.5%-2%, the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery are further improved.

[0339] As can be seen from the comparison between Examples 1-2 and Examples 3, 6, and 7, when the kernel's I... D / I G When the value is 0.7-1.0, the positive electrode active material has excellent initial specific capacity, and the cycle stability of the battery can be further improved.

[0340] As can be seen from Examples 1 and 8-10, when the phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, and manganese phthalocyanine, the battery cell exhibits excellent cycle stability, and the positive electrode active material exhibits excellent initial charge-discharge specific capacity. A comparison between Examples 1 and Examples 8-10 shows that when the phthalocyanine complex includes copper phthalocyanine, it helps to further improve the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0341] As can be seen from Examples 1 and 11, by treating the core and phthalocyanine complex using one or more of the following processes—dry mixing, ultrasonic processing, magnetron sputtering, dot coating, and dip coating—a positive electrode active material is obtained. The resulting battery cell exhibits excellent cycle stability, and the positive electrode active material demonstrates excellent initial charge-discharge capacity. A comparison between Examples 1 and 11 shows that treating the core and phthalocyanine complex using a dry mixing process to obtain the positive electrode active material helps to further improve the initial charge-discharge capacity of the positive electrode active material and the cycle stability of the battery.

[0342] As seen in Examples 1 and 12, the binder includes one or more of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives. The battery cell exhibits excellent cycle stability, and the positive electrode active material demonstrates excellent initial charge-discharge capacity. A comparison of Examples 1 and 12 shows that the binder using a blend of acrylonitrile-acrylic acid copolymer and polyethyleneimine helps to further improve the initial charge-discharge capacity of the positive electrode active material and the cycle stability of the battery.

[0343] As can be seen from the comparison between Example 1 and Example 13, dry mixing of the core and phthalocyanine complex yields the positive electrode active material; obtaining a mixture including the positive electrode active material, water and binder yields an aqueous positive electrode slurry, which helps to further improve the initial charge-discharge specific capacity of the positive electrode active material and the cycle stability of the battery.

[0344] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, The battery cell includes a positive electrode sheet, the positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer includes a positive active material, wherein the positive electrode sheet is an aqueous electrode sheet; The positive electrode active material includes a core and a coating layer covering at least a portion of the surface of the core. The coating layer includes a phthalocyanine complex. The core includes a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

2. The battery cell according to claim 1, characterized in that, The matrix is ​​selected from lithium-containing transition metal phosphates.

3. The battery cell according to claim 1 or 2, characterized in that, I of the positive electrode film D / I G It is 0.5-1.55, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

4. The battery cell according to any one of claims 1-3, characterized in that, The kernel's I D / I G It ranges from 0.7 to 1.

3.

5. The battery cell according to any one of claims 1-4, characterized in that, Based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.1%-2%.

6. The battery cell according to any one of claims 1-5, characterized in that, The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, which is 0.7-1.

0. And / or, The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, which is 1.0-1.

3.

7. The battery cell according to any one of claims 1-6, characterized in that, The phthalocyanine complex includes one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, or manganese phthalocyanine.

8. The battery cell according to any one of claims 1-7, characterized in that, The thickness of the coating layer is 150nm-500nm, and can be selected as 200nm-400nm.

9. The battery cell according to any one of claims 1-8, characterized in that, The volume distribution particle size Dv50 of the positive electrode active material is 0.5 μm-5 μm; and / or The volume distribution particle size Dv99 of the positive electrode active material is 10μm-15μm.

10. The battery cell according to any one of claims 1-9, characterized in that, The positive electrode film layer further includes a binder, which includes one or more of the following: methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

11. The battery cell according to any one of claims 1-10, characterized in that, The lithium-containing transition metal phosphate comprises components having the following general formula: Li m A a Fe x D d P y E e About z G g , The A element comprises at least one element selected from Al, Na, K, or Mg; the D element comprises at least one element selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti, or V; the E element comprises at least one element selected from B, S, Si, or N; the G element comprises at least one element selected from S, F, Cl, or Br; the m element is selected from the range of 0.5 to 1.15; the a element is selected from the range of 0 to 0.1; the x element is selected from the range of 0.5 to 1; the d element is selected from the range of 0 to 0.5; the y element is selected from the range of 0.5 to 1; the e element is selected from the range of 0 to 0.5; the z element is selected from the range of 3.5 to 4; and the g element is selected from the range of 0 to 0.

5.

12. A method for preparing a single battery cell, characterized in that, The preparation method includes at least the following steps: A positive electrode active material is obtained, the positive electrode active material comprising a core and a coating layer covering at least a portion of the surface of the core, the coating layer comprising a phthalocyanine complex; A mixture comprising the positive electrode active material and water is obtained to obtain an aqueous positive electrode slurry; Battery cells were prepared using the aforementioned aqueous cathode slurry; The core comprises a matrix and a carbon coating layer covering at least a portion of the surface of the matrix. The matrix is ​​selected from at least one of lithium-containing transition metal phosphates, sodium-containing polyanionic compounds, Prussian blue analogs, manganese-based compounds, vanadium-based compounds, or modified compounds thereof.

13. The preparation method according to claim 12, characterized in that, The matrix is ​​selected from lithium-containing transition metal phosphates.

14. The preparation method according to claim 12 or 13, characterized in that, The obtained positive electrode active material includes: The positive electrode active material is obtained by treating the core and the phthalocyanine complex using one or more of the following processes: dry mixing, ultrasonic processing, magnetron sputtering, dot coating, and dip coating.

15. The preparation method according to any one of claims 12-14, characterized in that, The preparation method includes at least the following steps: The core and the phthalocyanine complex are dry-mixed to obtain the positive electrode active material; A mixture comprising the positive electrode active material and water is obtained to obtain the aqueous positive electrode slurry.

16. The preparation method according to any one of claims 12-15, characterized in that, The kernel's I D / I G It is 0.7-1.3, where I D / I G I represents the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of the G peak at that location.

17. The preparation method according to any one of claims 12-16, characterized in that, Based on the total mass of the positive electrode active material, the mass percentage of the phthalocyanine complex is 0.1%-2%.

18. The preparation method according to claim 16 or 17, characterized in that, The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.1%-0.4% based on the total mass of the positive electrode active material, which is 0.7-1.

0. And / or, The kernel's I D / I G The mass percentage of the phthalocyanine complex is 0.5%-2% based on the total mass of the positive electrode active material, which is 1.0-1.

3.

19. The preparation method according to any one of claims 12-18, characterized in that, The phthalocyanine complexes include one or more of copper phthalocyanine, cobalt phthalocyanine, ruthenium phthalocyanine, platinum phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, iron phthalocyanine, and manganese phthalocyanine.

20. The preparation method according to any one of claims 12-19, characterized in that, The preparation method includes at least the following steps: The core and phthalocyanine complex are dry-mixed to obtain the positive electrode active material; A mixture comprising the positive electrode active material, water, and binder is obtained to obtain the aqueous positive electrode slurry.

21. The preparation method according to claim 20, characterized in that, The binder includes one or more of the following: methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyethyleneimine and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives.

22. The preparation method according to any one of claims 12-21, characterized in that, The mixture also includes one or more of conductive agents and dispersants.

23. The preparation method according to claim 22, characterized in that, The preparation method includes at least the following steps: The core and the phthalocyanine complex are first dry-mixed to obtain the positive electrode active material; The positive electrode active material and the conductive agent are subjected to a second dry mixing to obtain a first mixture; The first mixture, the dispersant, and water are first mixed to obtain a second mixture; The second mixture and the binder are mixed a second time to obtain the mixture, thus obtaining the aqueous positive electrode slurry.

24. The preparation method according to claim 23, characterized in that, The rotational speed of the first dry mixer is 300 r / min-1500 r / min, optionally 500 r / min-800 r / min; and / or, The second dry mixing speed is 300 r / min-1500 r / min, optionally 500 r / min-800 r / min; and / or, The rotational speed of the first mixing is 200 r / min-1800 r / min, optionally 800 r / min-1200 r / min; and / or, The rotational speed of the second mixing is 200 r / min-1800 r / min, and can be selected as 800 r / min-1200 r / min.

25. The preparation method according to any one of claims 12-24, characterized in that, The solid content of the aqueous positive electrode slurry is 50%-70%; and / or, The viscosity of the aqueous cathode slurry is 3000 mPa·s-9000 mPa·s.

26. An electrical appliance, characterized in that, The electrical device comprises a battery cell according to any one of claims 1-11 or a battery cell prepared by the preparation method according to any one of claims 12-25.